2018
DOI: 10.1123/ijsnem.2017-0313
|View full text |Cite
|
Sign up to set email alerts
|

Low Energy Availability Is Difficult to Assess but Outcomes Have Large Impact on Bone Injury Rates in Elite Distance Athletes

Abstract: We aimed to (a) report energy availability (EA), metabolic/reproductive function, bone mineral density, and injury/illness rates in national/world-class female and male distance athletes and (b) investigate the robustness of various diagnostic criteria from the Female Athlete Triad (Triad), Low Energy Availability in Females Questionnaire, and relative energy deficiency in sport (RED-S) tools to identify risks associated with low EA. Athletes were distinguished according to benchmarks of reproductive function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
253
5
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 230 publications
(289 citation statements)
references
References 33 publications
9
253
5
4
Order By: Relevance
“…It was reported that LEA induced through dietary restrictions resulted in significant decreases in leptin and insulin, but no changes in IGF‐1, ghrelin, testosterone, or free T 3 in recreationally active participants. Contrary to these results, evidence from cross‐sectional studies by Heikura et al and Hooper et al suggests significantly lower testosterone levels are associated with LEA (21 kcal/kg LBM/d) in both middle‐ and long‐distance runners and racewalkers. Additionally, McMurray et al reported elevations in human growth hormone (HGH) and significant decreases in IGF‐1 in wrestlers under conditions of LEA (<30 kcal/kg LBM/d).…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…It was reported that LEA induced through dietary restrictions resulted in significant decreases in leptin and insulin, but no changes in IGF‐1, ghrelin, testosterone, or free T 3 in recreationally active participants. Contrary to these results, evidence from cross‐sectional studies by Heikura et al and Hooper et al suggests significantly lower testosterone levels are associated with LEA (21 kcal/kg LBM/d) in both middle‐ and long‐distance runners and racewalkers. Additionally, McMurray et al reported elevations in human growth hormone (HGH) and significant decreases in IGF‐1 in wrestlers under conditions of LEA (<30 kcal/kg LBM/d).…”
Section: Resultsmentioning
confidence: 69%
“…Table summarizes the methods of assessing energy availability used across the cross‐sectional studies. Energy intake was measured via food frequency questionnaire or 3‐ to 7‐day food diaries using household measures or weighed records . One study measured energy intake 3 days per month .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A full gynaecological history is required, including menstrual and urogynaecology assessment, use of contraception, previous pregnancies and future pregnancy plans. While measurement of energy availability is difficult to assess and often inaccurate, it can be estimated using food diaries and exercise logs and can be supplemented with fitness technology equipment such as heart rate monitors.…”
Section: Clinical Assessmentmentioning
confidence: 99%